Prevalence of Postpartum Mental Health Problem in Siriraj Hospital - Nipan Boonyoung; Wiboolphan Thitadilok; Supachoke Singhakant (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective: To study the prevalence of postpartum mental health problem (postpartum MHP). Study design: Cross-sectional descriptive study. Materials and Methods: The 260 women in the first 48 hrs postpartum of > 24 weeks of gestation who were admitted at the postpartum ward, Siriraj Hospital during May 8th to August 2nd, 2008 were enrolled. After consent forms were done, they were asked to complete self-administered questionnaire including Thai GHQ-30 (mental health problem screening tool) and frequent psychosocial stressor forms. Main outcome measurement: Percentage of the positive Thai GHQ-30/ or probable of mental health problem. Results:The prevalence of postpartum mental health problem was 28.8%. There were statistic significances in some demographic and socioeconomic status: worrying about baby care, quantity of breast milk, number of marriage and postpartum complications, with adjusted OR 3.24 (95%CI 1.68, 6.25), 2.62 (95%CI 1.37, 5.01), 3.68 (95%CI 1.46, 9.27), 3.38 (95%CI 1.29, 8.85), respectively (P<0.05). The prognostic factors of psychosocial stressors were worrying about pregnancy and delivery, financial problem and bad events in life, with adjusted OR 5.91 (95%CI 2.00, 17.51), 3.57 (95%CI 1.49, 8.56), 2.23 (95%CI 1.01, 4.90), respectively. Conclusion:The prevalence of probable postpartum MHP was 28.8%. The prognostic factors of psychosocial stressors were worrying about pregnancy and delivery, financial problem and bad events in life.